Beberapa Faktor Yang Berhubungan Dengan Pemakaian Bahan Tambahan Pangan (BTP) Pada Produk Kerupuk Di Kecamatan Kaliwungu, Kabupaten Kendal - Pujiastuti, Zeta Rina; Sulistiyani, Sulistiyani; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2002)
ABSTRACT Background : The food is a primary human necessity. In Semarang there is sold many chips, which contain a prohibited additive substances (Rhodamin B, Auramin, Metanil Yellow and Borax). Method : This is observational research using survey method. Beside that, this research also conduct laboratory examination to chips that is produced by respondent. The number of population is 50 person. They are chips producers in Kaliwungu, Kendal. The number of sample 44 persons. Result : This research showed that 43.2% chip's producers are low economic level, 65.9% chip's producer had finished elementary school / not finished elementary school / no school, 38.6% chip's producer have a low knowledge about using food additive substances. The number of respondent who have a good attitude using the food additive substance 50%. The number of respondent who have no good practice 54.5%. The result of observation to consumer showed that 40% consumers choose the colored chips. The number of chip's producer who produce the colored chips are 30 person from 44 respondents. Based on the result of questioners for the goverment (Kendal Distric Health Office, Drug and Food Control Agency in Semarang), it is known that the founding to chip's producers specifically in Kaliwungu sub district is not effectif. Key word: Food Additive Substances, Chips and Kendal